PROFESSIONAL GUIDANCE IN THE CONTEXT OF EDUCATION AND BUSSINESS EXPANSSION - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2010)
This article deals with the relation between education and bussiness in profesional guidance. It gives the background for the development of professional guidance theory and system, it evaluates the development of Lithuanian business abroad and describes new challenges in profesional guidance. The increase of professional information and consulting has created favourable opportunities for Lithuanian business to expand abroad. Suggestions are given how to balance needs and offers for specialists and monitor these needs.Reasons are given for extension of the list of the participants in creation of the National professional guidance programme, including social partners – associated bussiness organizations – in this process.The system of professional guidance and preparation of specialists influences the success of business expansion, its competitiveness and possibility to react to a quickly changing enviroment. The development of international business creates new challinges for the national system of professional guidance.Improving the professional guidance system of Lithuania it would be positive to create the registre of the needs in specialists which would balance offers and needs in the market. Creating and developing the National system of professional guidance would be good to expand the number of its participants including interested business organizations and their associations.
Keywords: profesional information; profesional guidance; professional guidance programme; bussiness